IMPLEMENTASI PROGRAM EKOLOGI PARTISIPATIF DI KELURAHAN KOTA BARU KECAMATAN TANJUNG KARANG TIMUR BANDAR LAMPUNG - Aji, Gatot Bintoro Putra (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The implementation of a participatory ecology program is a strategic effort to create a clean, healthy, and sustainable environment through active community involvement. This study aims to describe the implementation of a community-based ecology program in Kota Baru Village, East Tanjung Karang. The program included planting 50 trees to increase green cover, creating biopore infiltration holes to reduce waterlogging and improve soil quality, and utilizing used cooking oil to create aromatherapy candles as an innovative solution for household waste management. Additionally, waste awareness campaigns, anti-bullying campaigns, environmental education, the distribution of street mirrors, participation in the commemoration of Indonesian Independence Day on August 17, and routine clean-up Fridays and afternoon exercise programs were integral to strengthening community ecological awareness. The implementation results showed increased community awareness of environmental management, reduced household waste generation, and the formation of social collaborations that strengthened solidarity among residents. With the involvement of various community groups, this program not only had ecological impacts, but also social and cultural ones. In conclusion, the implementation of a participatory ecology program in Kota Baru Village, East Tanjung Karang, serves as an effective model for community empowerment in preserving the environment while simultaneously improving the quality of life.